Towards a computer simulation of moisture separation in steam turbine systems - Houmani, Ahmed (ProQuest Dissertations & Theses, 1994)
Following the recent development of a dynamic model of a steam turbine (1), it is proposed to develop this further and to extend this work into other associated turbine components. The dynamic model was based on specified boundary conditions from which empirical relationships were derived. No account was taken of flow conditions within the turbine blades. The objective of the present research was to develop a computer model, using the computer code PHOENICS, which will predict the trajectories of moisture droplets in steam when subject to various flow patterns. In order to assess the results obtained by the computer simulation, experiments were carried out in the laboratory using small liquid drops in a curved duct. The air flow was laminar and irrotational. The computer predictions of droplet impact on the outside wall of the duct were within 1% of the measured positions. PHOENICS was also used to model a complicated three-dimensional geometry of a moisture separator used in CANDU reactors. However, the available computer storage was inadequate to achieve an accurate solution of even a laminar velocity field for this geometry and no realistic model of the turbulent droplet dispersion was available. Because of these two factors, the accurate prediction of moisture separator efficiency seems presently impractical.